Risks to the Human Rights Advocacy in African Constitutions - Markhgeym, Marina V.; Aristov, Evgeniy V.; Bezuglya, Anna A.; Novikova, Alevtina E.; Novikov, Andrey B. (International Journal of Criminology and Sociology, 2022)
This article presents the results of a comparative legal study of the texts of the constitutions of African states with a view to identifying the rules that minimize human rights risks. The research is based on a dialectical approach to the disclosure of legal phenomena and processes using general scientific (systematic and logical methods, analysis and synthesis) and specific scientific methods. African constitutions, in comparison with the constitutions of other states, and in particular European ones, contain a disproportionately large number of rules formalizing special human rights institutions. Typically, these are special councils, human rights commissions (Egypt, Morocco, and Tunisia) or certain categories of the population (three in Egypt, three in Morocco, one in the Central African Republic). In Morocco and Equatorial Guinea, both the Mediator and the Public Defender are established, respectively. The relevance of the study is due to the strategic objectives of creating a secure human rights status of the state, as well as the need to find and update theoretical, methodological, and practical approaches to protecting the rights and freedoms of a human and a citizen. Considering the rules of the African constitutional model of minimizing risks to human right advocacy, objectively in terms of quantity and quality, are considered hyperbolic.